Efficacy comparison of subcutaneous mastectomy using gasless and gas-insufflation single-port transaxillary approaches for gynecomastia - Zhang, Yuqing; Wang, Huiling; He, Jie; Wu, Yaqin; Liu, Rui; Xiao, Xiangyuqin; Zeng, Zheng; Zhang, Chaojie (Frontiers in Surgery, 2025)
BackgroundTo evaluate the clinical efficacy of gasless and single-port gas-insufflation transaxillary approaches in subcutaneous mastectomy for treating patients with gynecomastia (GM).MethodsThis study enrolled 46 patients with GM from May 2022 to October 2023. Twenty patients underwent subcutaneous mastectomy using the single-port gas-insufflation transaxillary approach (gas-insufflation group), while the other 26 patients received the same procedure through the gasless transaxillary approach (gasless group). This study further conducted inter-group comparisons in terms of the operation time, intraoperative bleeding, volume of postoperative drainage, timing of drainage tube removal, short-term postoperative complications, length of postoperative hospital stay, and medical costs.ResultsAll the 46 patients completed the operation successfully without conversion to open surgery, with confirmed diagnosis of GM through pathology. The average surgical time for the gasless group was significantly shorter than that of the gas-insufflation group (38.20 ± 10.773 vs. 62.96 ± 15.311 min, P < 0.01). There were no significant differences between groups in incision length, intraoperative bleeding, unilateral postoperative drainage volume, drainage tube retention time, length of postoperative hospital stay, or postoperative cosmetic outcomes (all P > 0.05).ConclusionThis study supports the clinical feasibility of using gasless transaxillary approach for subcutaneous mastectomy of patients with GM.